Representation of the Use of Sumbawa Language During the Covid 19 Pandemic - Suparman, Suparman (e-Journal of Linguistics, 2021)
This article discussed Representation of the Use of Sumbawa Language During the Covid 19 Pandemic. The purpose of this study is to describe of the sentences mening by using Sumbawa language, which it applied to give socialization about the corona virus 19 toward the Sumbawa societies. The location of this study was conducted in Sumbawa district, West Nusa Tenggara Province, Indonesia. Futhermore, the method of this study used the qualitative descriptive method. Then, the instruments used for collecting data implemented the documentation and photographic techniques. The result of this study classified into two points, the first the meaning of senteces related to the interpretation of Fairclough, found several sentences in the Sumbawa regional language, namely Patis Pang Bale Turit Pemerintah advice which means that stay at home following government advice. According to the government's advice, Tama Ko IGD means entering the Emergency Care Unit (IGD) at the hospital, and Tama Ko IGD means entering the Emergency Room (ER) at the hospital, and Fotomu Nempel Pang Buku Yasin means your photo is stuck in Yasin's book. The second the meaning of the use of the Sumbawa language related to Pearce which classifies it into three categories, namely icon, index and symbol. The iconic element in this study is in the form of a caricature of a medical worker, while the index is a sentence that uses the Sumbawa language 'ba meling nene nene mo!ompa kami ta!' which means 'it's up to you all! We are too tired to work! Furthermore, symbols are represented on images of Personal Protective Equipment (PPE) and images of masks used by medical personnel.